2019
DOI: 10.33963/kp.14888
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D deficiency with ventricular repolarization abnormalities

Abstract: BACKGROUND Vitamin D is involved in cardiac contractility and myocardial calcium hemostasis, and vitamin D deficiencies are known to cause various cardiovascular disorders and have been linked with sudden cardiac death. AIMS The aim of the study was to evaluate repolarization distribution, represented by QT interval, corrected QT interval (QTc), QT dispersion, Tpeak -to -Tend (Tp -e) interval, Tp -e/QTc ratio, JT interval, JT dispersion, and Tp -e/JTpeak ratio in children with vitamin D deficiency. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Vitamin D deficiency has been related to different cardiovascular disorders, including SCD [ 86 ]. Moreover, a decreased level of 25-OHD has been linked to structural and ionic channel remodeling, which may increase arrhythmic events [ 87 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D deficiency has been related to different cardiovascular disorders, including SCD [ 86 ]. Moreover, a decreased level of 25-OHD has been linked to structural and ionic channel remodeling, which may increase arrhythmic events [ 87 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In individuals taking antiepileptic drugs that cause vitamin D defi ciency, the QT interval has been shown to grow (42). On the other hand, in healthy individuals, vitamin D levels have been shown to increase in those with no vitamin D defi ciency or insuffi cient values such as Tp e, Tp e/QTc and Tp-e/JT (11).…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study of new repolarization anomalies as an indicator of malignant ventricular arrhythmias with serum vitamin D level (11), no such study involving children in the literature has been detected. In our study, the values of JTc and Tp-e/QT, which are ventricular repolarization markers of those with insuffi cient vitamin D levels compared to of those with suffi cient vitamin D levels, are increasing.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, very little is known about the relationship between cQT and 25(OH)D with contrasting results. Nalbant et al demonstrated that there is no difference in cQT between people with normal levels of 25(OH)D and those with low levels of 25(OH)D [57]; on the other hand, prolonged cQT duration and cQT dispersion have been observed in patients with vitamin D deficiency [57][58][59].…”
Section: Discussionmentioning
confidence: 99%